The bleaching limits of IRSL signals at various stimulation temperatures and their potential inference of the pre-burial light exposure duration - Zhang, Jingran; Guralnik, Benny; Tsukamoto, Sumiko; Ankjærgaard, Christina; Reimann, Tony (Frontiers in Earth Science, 2023)
Infrared Stimulated Luminescence (IRSL) techniques are being increasingly used for dating sedimentary feldspars in the middle to late Quaternary. By employing several subsequent stimulations at increasing temperatures, a series of post-IR IRSL (pIRIR) signals with different characteristics (stability and bleachability) can be obtained for an individual sample. It has been experimentally demonstrated that higher-temperature pIRIR signals are more stable, but they tend to exhibit larger residual doses up to few tens of Gy, potentially causing severe age overestimation in young samples. In this study we conducted comprehensive bleaching experiments of IRSL and pIRIR signals using a loess sample from China, and demonstrated that non-bleachable components in the IR (and possibly pIRIR) signals do exist. The level of such non-bleachable signal shows clearly positive correlation with preheat/stimulation temperature, which further supports the notion that lower temperature pIRIR are advantageous to date young samples and sediments especially from difficult-to-bleach environments. These results display a potential in constrain the pre-burial light exposure history of sediment utilizing multiple feldspar post-IR IRSL (pIRIR) signals. For the studied loess sample, we infer that prior to its last burial, the sample has received an equivalent of >264 hours exposure to the SOL2 simulator (more than two thousand hours of natural daylight).